EKUALISASI PEREDARAN USAHA PADA SPT PPN DAN SPT PPH DAN PERILAKU KEPATUHAN PAJAK INDUSTRI PENGOLAHAN TEMBAKAU (STUDI KASUS PADA PT. XYZ) - Yonathan Kristian; Elia Mustikasari (Behavioral Accounting Journal, 2018)
This research has a purpose to find out how to perform equalization or reconciliation between The Monthly Value Addes Tax Return and Corporate Income Tax Return and taxpayer compliance behavior to record the differences. This research was conducted at the cigarette company that has a different VAT rules with other industries. This research is qualitative research using the case studymethod. The data collection method used isdocumentation and semi structured interviews. The base theory of this research are using tax regulation in Indonesia and the Theory of Planned Behavior to examine how tax managers compliance behavior who represent PT. XYZ to record the diferences of the. The results of this research is a way and new knowledge on how to perform equalization VAT and income tax in the cigarette companies and the differences that were found have been recorded in accordance with what is believed to be comply by PT. XYZ who most influenced by a high tax sanctions.